Hubungan antara Ketahanan Pangan Rumah Tangga dengan Kejadian Underweight di Kecamatan Jelbuk Kabupaten Jember - Dzakiyah Wijaya (Fakultas Kesehatan Masyarakat, 2024)
Underweight is a category of nutritional status in children under five with Z Score BB/U <-2 SD. Survei Status Gizi Indonesia (SSGI) in 2022 showed that the incidence of underweight in Indonesia reached 17.1%, meanwhile underweight in Jember reached 10.96%. The highest prevalence of underweight in Jember is at Jelbuk which reached 18.7%. This figure remains a source of concern and a pressing issue that requires prompt attention. One aspect that affects underweight is household food security. Household foor security is a family’s ability to ensure that all household members have enough food. According to the database by Food Scurity and Vulnerability Atlas (FSVA), the food security category in Jember was considered resistant (Priority 5). However, Jelbuk, a sub-district in Jember, fell under the category of somewhat vulnerable (Priority 3). Precisely in three villages in Jelbuk, that are Jelbuk, Sukojember, and Sukowiryo. Therefore, it was necessary to specifically study household food security in some of these villages in Jelbuk, Jember. The purpose of this study was to describe the characteristics of children under five and their families, as well to determine the correlation of household food security and the incidence of underweight in Jelbuk, Jember. The design of this research was observational analytic with cross sectional. Data were collected through interviews with adults in the families of children under five who attended posyandu in Jelbuk, Sukowiryo, and Sukojember. Household food security was measured using the Jonsson & Toole modified by Maxwell, crossing the indicators of Energy Adequacy Rate and Food Expenditure Share of households. Energy Adequacy Rate was obtained through a 2 x 24-hour food recall process, and PPP through interviewed with respondents regarding food expenditure and total household expenditure. Data were presented in narrative and tables. ix The results showed 53.8% of children were ≥ 24 months old and 54.7% were female. Then, most of the families had a small type (≤4) as much as 60.4%. The family income was mostly < Rp 2,665,392. Fathers who worked were 99.1%, while the majority of mothers did not work by total 94 and 49% of mothers education graduated from elementary school. Household food security status in children under five reached 44.3% have food vulnerable status, 34.9% food resistant status, 12.3% food insecure, and 8.5% got food insufficient status, while nutritional status (BB/U) showed that most toddlers were not underweight (84%). Meanwhile, the results of the analysis of the correlation between household food security and the incidence of underweight with the spearman test p-value significance value of 0,007 means, household food security status was significantly associated with the incidence of underweight in Jelbuk, Jember. The conclusion of this study was that household food security in children under five in Jelbuk, Jember the majority have food vulnerable status, and there was no relationship between household food security and the incidence of underweight. Suggestions that can be given are for the Puskesmas Jelbuk should to hold food empowerment training for the community by utilizing yard land. Dinas Kesehatan Kabupaten Jember provides PMT to children underweight with food insecure families. Dinas Ketahanan Pangan Kabupaten Jember needs to carry out monitoring to guarantee teh timely provision of food assistance. Future researchers are advised to conduct research using children food intake and employ food scurity instruments that align with community characteristics.
Reaploud Repository Hasyim April 2026
Keywords: UNDERWEIGHT; KETAHANAN PANGAN; Rumah Tangga